2016
DOI: 10.1080/17458080.2016.1184766
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of biosynthesised copper nanoparticles evaluated against red root-rot disease in tea plants

Abstract: The synthesis of metal nanoparticles is an emerging area of advanced research and technology with potential application in plant protection. In the current study, with an eco-friendly approach, a convenient method was adopted, where copper nanoparticles are biosynthesised extracellularly by using Streptomyces griseus. Further, the existence of nanoparticles was confirmed by UVÀvisible spectroscopy, transmission electron microscopy, X-ray diffraction analysis and Fourier transform infrared spectroscopy characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(45 citation statements)
references
References 15 publications
2
43
0
Order By: Relevance
“…Many applications involve the traditional role of Cu as a conductor, such as conductive dyes (Albrecht et al, 2016;Hokita et al, 2015;Tam and Ng, 2015;Kharisov and Kharissova, 2010;Tsai et al, 2015;Gopalan et al, 2016) or heat transfer fluids (Park et al, 2015;Montes et al, 2015;Azizi et al, 2016;Rizwan-ul-Haq et al, 2016), but the use of nano-Cu is rapidly expanding into novel applications such as catalysts in organic synthesis (Dugal and Mascarenhas, 2015;Lennox et al, 2016;Barot et al, 2016), sensors (Albrecht et al, 2016;Tsai et al, 2015;Gopalan et al, 2016;Brahman et al, 2016;Pourbeyram and Mehdizadeh, 2016), solar cells (Yoon et al, 2010;Parveen et al, 2016;Shen et al, 2016), light-emitting diodes , hydrogen generation (Liu et al, 2015a;Liu et al, 2015b), and drug delivery (Woźniak-Budych et al, 2016). Based on the antifungal and antimicrobial properties of Cu + 2 , Cu NPs are actively being developed for applications in agriculture and food preservation (Park et al, 2015;Montes et al, 2015;Dugal and Mascarenhas, 2015;Ray et al, 2015;Kalatehjari et al, 2015;Ponmurugan et al, 2016;Maniprasad et al, 2015;Majumder and Neogi, 2016;Villanueva et al, 2016), textiles (Majumder and Neogi, 2016;Sedighi and Montazer, 2016), ...…”
Section: Introductionmentioning
confidence: 99%
“…Many applications involve the traditional role of Cu as a conductor, such as conductive dyes (Albrecht et al, 2016;Hokita et al, 2015;Tam and Ng, 2015;Kharisov and Kharissova, 2010;Tsai et al, 2015;Gopalan et al, 2016) or heat transfer fluids (Park et al, 2015;Montes et al, 2015;Azizi et al, 2016;Rizwan-ul-Haq et al, 2016), but the use of nano-Cu is rapidly expanding into novel applications such as catalysts in organic synthesis (Dugal and Mascarenhas, 2015;Lennox et al, 2016;Barot et al, 2016), sensors (Albrecht et al, 2016;Tsai et al, 2015;Gopalan et al, 2016;Brahman et al, 2016;Pourbeyram and Mehdizadeh, 2016), solar cells (Yoon et al, 2010;Parveen et al, 2016;Shen et al, 2016), light-emitting diodes , hydrogen generation (Liu et al, 2015a;Liu et al, 2015b), and drug delivery (Woźniak-Budych et al, 2016). Based on the antifungal and antimicrobial properties of Cu + 2 , Cu NPs are actively being developed for applications in agriculture and food preservation (Park et al, 2015;Montes et al, 2015;Dugal and Mascarenhas, 2015;Ray et al, 2015;Kalatehjari et al, 2015;Ponmurugan et al, 2016;Maniprasad et al, 2015;Majumder and Neogi, 2016;Villanueva et al, 2016), textiles (Majumder and Neogi, 2016;Sedighi and Montazer, 2016), ...…”
Section: Introductionmentioning
confidence: 99%
“…Copper is an essential micronutrient that is incorporated into many proteins and enzymes, and is also important in the health and nutrition of plants [21] and in photosynthetic reactions [22]. This element, in the form of nanoparticles, has also been shown to have a strong antifungal activity [23]. It has been demonstrated that Cu NPs and Ag NPs, applied both individually and together, help in the inhibition of pathogenic fungi such as Alternaría alternata and Botrytis cinera [24].…”
Section: Introductionmentioning
confidence: 99%
“…As copper is as an essential constituent in plants, CuNPs have been utilized as antimicrobial agents for biocidal activity [15,16]. In addition, CuNPs are used in agriculture as an effective nano-metallic fungicide application in crops to protect against fungal diseases [17,18].…”
Section: Introductionmentioning
confidence: 99%